PENGARUH KONSENTRASI ASAM KLORIDA DAN LAMA PERENDAMAN TERHADAP SIFAT FISIK DAN KIMIA GELATIN TULANG IKAN TUNA (Thunnus albacare) - Masrukan, Masrukan; Santoso, Umar (Universitas Widya Mataram, 2016)
Type A gelatin was extracted from partial hydrolysis of collagen from tuna fish bone. The experiment was conducted to determine the effect of hydrochloride acid solution and soaking time on physical and chemical properties of tuna fish bone gelatin and to determine optimum conditions for extraction of tuna fish bone gelatin which is based on the highest yield and gel strength. The experiment used randomized complete block design (RCBD) with two factors. The first factor was concentration of hydrochloric acid consisting of 3 level (1, 3, and 5% v/v) and the second factor was soaking time (24, 48, and 72 hours). The results showed that concentration of hydrochloric acid and soaking time significantly affect at the physical and chemical properties of tuna fish bone gelatin. The optimum condition obtained the treatment of gelatin was concentration of hydrochloric acid 3% and soaking time 72 hours. Physical and chemical properties of gelatin from tuna fish bone, which is 120.37 gram Bloom gel strength; viscosity 4.75 cP; melting point 20.37 ° C; color was yellowish brown, moisture content 11.85%, protein content 80.90%.; fat content 2.73% and ash content 8.12%.